2017
DOI: 10.3389/fpls.2017.00358
|View full text |Cite
|
Sign up to set email alerts
|

Pentaploid Wheat Hybrids: Applications, Characterisation, and Challenges

Abstract: Interspecific hybridisation between hexaploid and tetraploid wheat species leads to the development of F1 pentaploid hybrids with unique chromosomal constitutions. Pentaploid hybrids derived from bread wheat (Triticum aestivum L.) and durum wheat (Triticum turgidum spp. durum Desf.) crosses can improve the genetic background of either parent by transferring traits of interest. The genetic variability derived from bread and durum wheat and transferred into pentaploid hybrids has the potential to improve disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 99 publications
0
20
0
Order By: Relevance
“…Three of the originally-sown plants did not grow to maturity. This is expected as sterility is often associated with the incompatibility among the tetraploid and hexaploid crosses [ 20 , 21 ]. The F 2 population had a height distribution skewed towards the parent Icaro ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the originally-sown plants did not grow to maturity. This is expected as sterility is often associated with the incompatibility among the tetraploid and hexaploid crosses [ 20 , 21 ]. The F 2 population had a height distribution skewed towards the parent Icaro ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In crosses involving parents of different ploidy levels, it has been shown that using the higher ploidy level genotype as the maternal parent is generally more successful in producing viable F 1 progeny (Ramsey and Schemske, 1998; Kalous et al, 2015). In pentaploid wheat crosses, the hexaploid parent is usually used as the female parent (Padmanaban et al, 2017a; Padmanaban et al, 2017b) and thus, the hexaploid WMI lines were used here as the female parent. Viable F 1 seeds were obtained with both durum wheat parents, Om Rabi 5 and Karim.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of R genes from wild species by classical breeding is time-consuming (often more than 10 years), and often associated with linkage drag. In addition, crosses between wild species and wheat can be complicated due to differences in ploidy level (Padmanaban et al, 2017). The native R genes, including their native promoters and terminators, could be used for transformation of commercially cultivated varieties.…”
Section: Cisgenesis and Intragenesismentioning
confidence: 99%